Strengthening urban water resilience in response to climate change - HWANG, Jintea (KDI School, 2024)
To improve the resilience of cities to respond to climate change and environmental pollution, which are becoming more severe around the world, this paper proposes improvement measures for urban water cycle restoration facilities centered on the new city of Busan (Eco Delta City) to restore a healthy urban water cycle and introduces a review method for spreading to other regions.Water circulation facilities, which are urban infrastructure, can act as an obstacle to the formation of social consensus for the entire city, such as the refusal of local governments to take over and excessive management costs, as has been confirmed in various cases recently. While the need and motivation for water cycle urban policies are clear and valid to solve urban water problems due to recent climate change, to lead to more realistic results experienced by local governments and citizens, we would like to explore practical ways for policy implementers to move beyond theoretical limitations and consider the needs of various stakeholders and cooperate with each other. In the end, the success of urban water cycle recovery policies requires the development of new evaluation techniques, including technical hardware. To introduce collaborative software that can reasonably reflect the needs of various stakeholders, it is necessary to improve the understanding of the process of urban development that can be understood by various actors in urban development, and to enhance the implementation of water cycle policies by providing improvement effects and numerical analysis results based on specific regions to secure the need for introduction.
Thesis(Master) -- KDI School: Master of Public Management, 2024
Keywords: Water resources development--Korea (South); Municipal water supply--Korea (South)